2017
DOI: 10.1097/jnn.0000000000000258
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an Early Mobility Pathway in Neurointensive Care Unit Patients With External Ventricular Devices

Abstract: The mobilization of patients with EVDs is safe and feasible; it may be associated with earlier mobilization, reduced ICU LOS, and better discharge disposition. No major complications were attributable to early mobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 4 publications
0
44
2
2
Order By: Relevance
“…However, to minimize the contribution of immobilization on complication rate, early mobilization protocols could be beneficial and appear to be safe [38,61,62]. Probably, the beneficial effect only applies to complications with a strong correlation to immobilization.…”
Section: Medical Complications and Their Relation To External Csf Dramentioning
confidence: 99%
“…However, to minimize the contribution of immobilization on complication rate, early mobilization protocols could be beneficial and appear to be safe [38,61,62]. Probably, the beneficial effect only applies to complications with a strong correlation to immobilization.…”
Section: Medical Complications and Their Relation To External Csf Dramentioning
confidence: 99%
“…Subjects for Phases I and II were prospectively identified from an IRB-approved cohort of SAH patients admitted to the Neuro ICU between 2014 and 2016. Phase I lasted for 12 months, from 2014 to 2015, and was characterized by use of a PT/OT-driven protocol [13]. Mobilization occurred only during formal PT/OT sessions with continuous presence of both the therapist and the bedside nurse.…”
Section: Phase Imentioning
confidence: 99%
“…Although mobilizing patients with invasive devices carries inherent risk, the consequences of prolonged bed rest, including significant muscle wasting and reduced functional status, are profound [23,24]. Recent literature has demonstrated that early mobilization in the ICU can be a safe and feasible intervention, with few adverse events recorded [7,13]. Both therapy-driven and nursedriven protocols have been studied with similar safety outcomes [5,19,[25][26][27][28][29][30][31][32][33][34].…”
Section: Safety/complicationsmentioning
confidence: 99%
“…Recent studies support the safety and feasibility of progressive mobility from in-bed activity to out of bed and walking in NCCU patients with external ventricular drainage (EVD) [14][15][16]. In nearly all reports, progressive mobility interventions begin at the time that patients demonstrate arousal, awareness and are able to follow motor commands, resulting in significant delays until mobility interventions can be implemented, if at all [17][18][19].…”
Section: Discussionmentioning
confidence: 99%